KONSTRUKSI KODE CROSS BIFIX BEBAS TERNAIR BERPANJANG GENAP UNTUK MENGATASI MASALAH SINKRONISASI FRAME - Moh. Affaf; Zaiful Ulum (Lembaga Penelitian dan Pengabdian Masyarakat - Universitas Teknologi Digital Indonesia, 2017)
In order to guarantee the synchronization between a transmited data by transmitter and received data by receiver can be done by periodically inserting a fixed sequence into the transmited data. It is one of the main topic in digital communication systems which called Frame Synchronization. Study of Cross Bifix Free Codes arise to solve Synchronization’s problem via distributed sequence’s method which introducted first in 2000. A Cross Bifix Free Codes is a set of sequences in which no prefix of any length of less than to of any sequences is the sufix of any sequence in the set. In 2012, a Binary Cross Bifix Free Codes was constructed by using Dyck path. In 2017, a Ternary Cross Bifix Free Codes with odd lenght was constructed, , by generalize the construction of binary cross bifix free. In this paper, will be constructed Ternary Cross Bifix Free Codes for even length, , by expand the construction of Binary Cross Bifix Free Codes.